Taking a leap towards a real world macroeconomics teaching - Ioannou, S; Bullio Mattos, O (Inderscience, 2018)
Despite the centrality of finance in the workings of the modern capitalist economy, macroeconomics is still taught with no serious consideration of monetary and financial dynamics. This has become even more puzzling in the light of the recent financial crisis. Our paper discusses a more pluralistic framework for teaching basic macroeconomics, inclusive of some of the most important ideas of Keynes on interest and money. The incorporation of Keynesian economics not only allows students to broaden their thinking in considering alternative answers to given questions; it also reshapes the questions themselves. In doing so, it changes the framework within which students come to think of policy. Focusing on the case of monetary policy, we point out the commonality between the mainstream teaching paradigm and the actual mindset that influences policy making. Furthermore, we discuss the ways in which the scope and aims of monetary policy are altered under a Keynesian/Minskyan framework.